2012
DOI: 10.3846/16486897.2012.695738
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between aesthetic preferences of river and landscape characters

Abstract: Some landscape characters put great influences on the aesthetic preferences of a river. Finding out these characters will provide for river landscape design and management with explicit keystones. In this paper, 23 sample areas of rivers were selected in Xuzhou, China, and 15 landscape characters of rivers were identified. The photos taken at the sample areas were as stimuli, and undergraduate students were respondents. The results demonstrate that the aesthetic preferences of photos judged one-by-one and judg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…Zhao at al. [5] obtained other results where species, variety of trees and the presence of water plants constituted negative predictive factors for aesthetic preferences for urban rivers.…”
Section: Function 2 Clearly Discriminates Between Classes Vl and M Wmentioning
confidence: 86%
See 3 more Smart Citations
“…Zhao at al. [5] obtained other results where species, variety of trees and the presence of water plants constituted negative predictive factors for aesthetic preferences for urban rivers.…”
Section: Function 2 Clearly Discriminates Between Classes Vl and M Wmentioning
confidence: 86%
“…Similarly, the MULBO model [3], which is based on abiotic, biotic and socio-economic factors, omits the aesthetic landscape function. Zhao and co-workers [5] Fig.1. The research area (author study).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Researchers ask participants to select or score their favorite photographs to determine the variety of landscape preferences (Bulut and Yilmaz, 2008;Canas et al, 2009;Tveit, 2009;Sevenant and Antrop, 2010;Kurdoglu and Kurdoglu, 2010;Howley, 2011;Ozkan, 2014). There are many visual quality evaluation studies on various habitat types, including those on rural landscapes (Arriaza et al, 2004;Rogge et al, 2007), wetlands, rivers, lake-wetlands (Meitner, 2004;Bulut and Yılmaz, 2009;Zhao et al, 2013), forests (Eroğlu and Acar, 2011), agricultural landscapes (Matthies et al, 2010, Acar andEroğlu, 2010 ), roadside and road corridors (Akbar et al, 2003;Clay and Smidt, 2004;Eroğlu at al., 2016), rocky habitats (Acar et al, 2013;Acar and Sakıcı, 2008), coastal landscape areas (Kalın, 2004;Ak, 2010), and mountainous areas (Eroğlu, 2012;Kalın et al, 2014). Most of these studies have attempted to assess the different settings found in a single habitat or to determine their seasonal changes.…”
Section: Introductionmentioning
confidence: 99%